Changes in sexual risk behavior among MSM participating in a research cohort in coastal Kenya. (December 2015) - Möller, Lisanne M.; Stolte, Ineke G.; Geskus, Ronald B.; Okuku, Haile Selassie; Wahome, Elizabeth; Price, Matt A.; Prins, Maria; Graham, Susan M.; Sanders, Eduard J.
Abstract : Objective: To describe changes in sexual risk behavior among Kenyan MSM who received regular risk reduction counseling (RRC). Design: Data were derived from two cohorts of HIV-1-negative and HIV-1-positive MSM in Kenya. Behavioral data were collected at enrollment and at monthly or quarterly scheduled follow-up visits. At each visit, RRC was provided to all men and HIV-1 testing to seronegative men. Methods: Random effects logistic and Poisson regression models with time since study entry as main variable of interest were used to evaluate changes in number of sex partners and unprotected sex in the past week, and insertive, receptive, and unprotected anal intercourse in the past 3 months. Analyses were adjusted for HIV-1-status, calendar year of follow-up, and several baseline characteristics. Trends over follow-up time were allowed to differ by HIV-1-status. Men were censored when they seroconverted for HIV. Results: Number of regular and casual sex partners and unprotected anal intercourse decreased in both HIV-1-negative and HIV-1-positive men. Unprotected sex with both regular and casual sex partners decreased more strongly early in follow-up in HIV-1-positive men than in HIV-1-negative men. Decreases in insertive anal intercourse were found for HIV-1-positive men only, whereas decreases in receptive anal intercourse were found for HIV-1-negative men only. Conclusion: MSM who were regularly exposed to RRC showed some reductions in sexual risk behavior, but it is uncertain if these reductions are sustained over time. As HIV-1 incidences in Kenyan MSM are very high, RRC should be supported by comprehensive biomedical interventions. Abstract : Supplemental Digital Content is available in the text